(untitled) (Innovative professional education, 2024)
The article considers the features of distance and blended learning in vocational education institutions. Distance and blended learning is especially relevant today in the training of skilled workers. The experience of the pedagogical staff of VPU №25 of Khmelnytsky on the introduction of distance and blended learning in the educational environment is presented.